2017
DOI: 10.1016/j.cjtee.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic pattern of paediatric supracondylar fractures of humerus in a teaching hospital of rural India: A prospective study of 263 cases

Abstract: PurposeThis prospective study aimed to investigate the epidemiologic parameters of supracondylar humeral fractures in children admitted to a teaching institution of a developing country primarily catering to rural population, to find any preventable cause of such injuries.MethodsAll suspected cases of supracondylar humeral fracture reporting to emergency or outpatients department were analysed for various epidemiologic parameters including age, sex, laterality, time of presentation, associated injuries, neurov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
(19 reference statements)
2
18
0
Order By: Relevance
“…From the distribution according to sex in previous study from Esen and Sapmaz and Anjum et al, male patients sustained more elbow fractures compared than female patients [5], [6]. This is in line with the result of our study in which the male patients dominantly suffered elbow fractures than the female patients while a retrospective study about pediatric elbow fractures conducted by Emery et al showed no differences in the demographic pattern of sex [7].…”
Section: Discussionsupporting
confidence: 91%
“…From the distribution according to sex in previous study from Esen and Sapmaz and Anjum et al, male patients sustained more elbow fractures compared than female patients [5], [6]. This is in line with the result of our study in which the male patients dominantly suffered elbow fractures than the female patients while a retrospective study about pediatric elbow fractures conducted by Emery et al showed no differences in the demographic pattern of sex [7].…”
Section: Discussionsupporting
confidence: 91%
“… 1999 , Anjum et al. 2017 , Lempesis et al. 2017 ) and with a higher incidence during the warmer than during the colder season (Tiderius et al.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent fractures in pediatric supracondylar fracture have been reported up to 5% in the literature. 13 Average duration between day of injury and day of surgery was 5.2 days (2-14 days). Delayed presentation is not uncommon in our hospital due to lack of transport, uneven geographical topography and initial management by traditional bonesetter.…”
Section: Discussionmentioning
confidence: 99%